Psychosocial interventions for anxiety disorders in adults: evidence mapping and guideline appraisal - Huang, Chuxian; Liu, Xiao; Liu, Yue; Luo, Chen; Cai, Jiajia; Wang, Yanmei; Chen, Jue; Shi, Zhongying; Jin, Xiaochao (Frontiers in Psychiatry, 2025)
IntroductionThis systematic review summarizes the recommendations related to psychosocial interventions for anxiety disorders included in existing guidelines and compares their differences.MethodsComputer-based searches were conducted to identify relevant guidelines on psychosocial interventions for anxiety disorders from domestic and international guideline websites, professional association websites, and other relevant databases. The guidelines’ quality was evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool.ResultsFourteen guidelines from nine countries were included, with AGREE II scores ranging between 64.4%–96.3%. The specific recommendations were synthesized into a single evidence map, revealing that cognitive behavioral therapy demonstrated strong support for treating generalized anxiety, panic, and social anxiety disorders. Conversely, eye movement desensitization and reprocessing, exposure therapy, and virtual reality exposure therapy were not recommended for panic disorder. Additionally, no guidelines provided any recommendations for psychosocial interventions for separation anxiety disorder.DiscussionGuidelines on psychosocial interventions for adult anxiety disorders vary remarkably concerning their quality and recommended suggestions. Future guideline development or updates should strictly adhere to standardized development processes. Additionally, researchers should double their efforts to continuously explore and validate the efficacy of various psychosocial interventions in anxiety populations.Sytematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250654358, PROSPERO, identifier CRD420250654358.